„Дружба” и „друг” в языковой картине мира (на материале паремиологических трансформ) - Tomasz J. Szutkowski (Studia Rossica Posnaniensia)
In the paper, based on the material of paremiological units (proverbs, aphorisms, phrases), concepts of friendship and friend have been discussed. The carried out analyses afforded more accurate observation of the language picture of the world in the social communication, whose base – in that case – was friendship which was so richly established in the European aphoristics. Via transformations of established paremiological constructions the users of Russian language included in them not rarely very critical view of the modern interpersonal relations.